INTERNET AND RELIGION: Digital Deities and Technoshamanism Changing Our Understanding of Spirituality - Tjerlang Munir; Sutrisno Sutrisno; Marthin Steven Lumingkewas (Sekolah Tinggi Teologi Moriah, 2023)
The internet has grown in importance as a platform for religious speech and practice, with some considering it a suitable medium for magical experimentation and rituals. Sects and religious meetings have also found a new home in digital networks. Some religious societies have opted to shift their activities online, resulting in digital religion and hyper-mediated religious experiences. The use of digital technology has also fueled religious imagination, notably in the context of animism. The use of digital technology for spiritual reasons, known as technoshamanism, is becoming increasingly popular among neopagans, occultists, and New Agers. As a result, the internet has become a haven for digital deities and technoshamanism, opening new avenues for religious expression and practice. With this context in mind, the research focuses on digital religion, with researchers discussing how digital deities and technoshamanism are changing our understanding of spirituality. The purpose of this research explores how the internet and religion are transformed in the move from offline to online contexts into digital deities and technoshamanism. The rise of digital deities and technoshamanism is altering our perception of spirituality. As a result, the influence of digital deities and technoshamanism on the nature of spirituality is still being explored and researched, with consequences for both conventional religious organizations and the larger cultural environment. The research method of this study is library research, to gather information from books, journals, and online libraries.